A comprehensive overview of artificial intelligence applications in basketball - Agbozo, E.; Pandya, K.; Jovanovic, P.; Suvorova, E. A. (Journal of Physical Education and Sport, 2024)
The sports industry is progressively embracing technological advancements, and artificial intelligence stands out as a prominent innovation. Basketball in particular, has captured the interest of the real-time analytics and data science community. With the development, deployment, and experience of AI models by both viewers and players, it is crucial to provide a comprehensive summary of AI applications in basketball. This review is performed based on literature sourced from Web of Science and Dimensions databases, where articles were thoroughly examined to identify AI use cases. The study was backed by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework and furthermore utilized computational literature review as well as bibliometric analysis techniques for knowledge extraction purposes. Our results revealed that the area of sports analytics is gaining momentum and AI in the basketball world has more adoption in China, USA, Australia, Canada, Italy and Spain from a research perspective. Our study offers contributions to theory and practice in the sports science and applied AI domains.